Antibacterial activity of green fabricated silver-doped titanates - A. C. Ha; T. Nguyen; P. A. Nguyen; V. M. Nguyen (Тонкие химические технологии, 2022)
Objectives. The study aimed to synthesize the multifunctional materials silver-added titanates via reduction of sol-gel fabricating titanates (Fe2TiO5 and NiTiO3) with Jasminium subtriplinerve Blume leaf extract.Methods. The physicochemical characteristics of the obtained materials were determined by X-ray diffraction, energy dispersive X-Ray spectroscopy, Raman spectroscopy, Brunauer–Emmett–Teller specific surface area, scanning electron microscopy, and UV–Vis absorption spectroscopy.Results. The results demonstrated good dispersion of silver on the surface of Fe2TiO5 and NiTiO3 to create photocatalysts with two light-absorbing regions. The obtained materials were applied as antibacterial agents in polluted water. The Ag–Fe2TiO5 (Ag–FTO) samples showed better properties and antibacterial activity than Ag–NiTiO3 (Ag–NTO) due to the better dispersion of silver nanoparticles on the FTO surface. Besides, the antibacterial results exhibit increased inhibiting activity against gram-negative (−) bacteria as compared with gram-positive (+) bacteria.Conclusions. Nanomaterials Fe2TiO5 and NiTiO3 added Ag were successfully synthesized. These materials showed excellent inhibition against Baccilus cereus, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, and Staphylococcus aureus. Additionally, the Ag–Fe2TiO5 samples showed much better antibacterial activity than the Ag–NiTiO3 sample.